PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN ARTIFICIAL INTELLIGENCE TERHADAP HASIL BELAJAR PERSAMAAN LINEAR SATU VARIABEL SISWA SMP - Stella Fidia; Ketut Sarjana; Junaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Discovery Learning model using AI on student learning outcomes in single variable linear equations in grade VIII at SMP Negeri 7 Mataram in the 2025/2026 academic year. This study uses a quantitative method with a quasi-experimental design. The population in this study consisted of all 410 eighth-grade students at SMP Negeri 7 Mataram in the 2025/2026 academic year. The sample in this study consisted of 83 students selected using cluster random sampling. The instruments used in this study were observation sheets, post-test questions, teaching modules, and student worksheets. The results of data analysis using the t-test showed that the value  dan . Thus, there was a difference in the average post-test scores of students between the experimental class and the control class, where the average post-test score of students in the experimental class was 77.53, higher than the average score of students in the control class, which was 71.02, with an effect size of d=2.7. Thus, it can be concluded that there is an effect of the Discovery Learning model using AI in the form of the ChatGPT application on student learning outcomes in the subject of single-variable linear equations in class VIII of SMP Negeri 7 Mataram in the 2025/2026 academic year.